2009
DOI: 10.1371/journal.pone.0007551
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Profiling in LRRK2-Related Parkinson's Disease

Abstract: BackgroundMutations in LRRK2 gene represent the most common known genetic cause of Parkinson's disease (PD).Methodology/Principal FindingsWe used metabolomic profiling to identify biomarkers that are associated with idiopathic and LRRK2 PD. We compared plasma metabolomic profiles of patients with PD due to the G2019S LRRK2 mutation, to asymptomatic family members of these patients either with or without G2019S LRRK2 mutations, and to patients with idiopathic PD, as well as non-related control subjects. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
153
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(158 citation statements)
references
References 41 publications
4
153
1
Order By: Relevance
“…73 The kinase activity, GTP-binding (GTPase) and WD40 domain of RIP7 are all reported to be implicated in RIP7's neurotoxicity. [74][75][76][77][78] Although much effort has been made in searching for the molecular mechanism underlying RIP7's function, [79][80][81][82][83][84][85] the pathogenesis of RIP7 mutations in Parkinson's disease remains unclear.…”
Section: Rip6 and Rip7mentioning
confidence: 99%
“…73 The kinase activity, GTP-binding (GTPase) and WD40 domain of RIP7 are all reported to be implicated in RIP7's neurotoxicity. [74][75][76][77][78] Although much effort has been made in searching for the molecular mechanism underlying RIP7's function, [79][80][81][82][83][84][85] the pathogenesis of RIP7 mutations in Parkinson's disease remains unclear.…”
Section: Rip6 and Rip7mentioning
confidence: 99%
“…PD is mostly idiopathic but can also be of genetic origin. Two metabolic profiling studies of PD patients reveal decreased plasmatic levels of the antioxidant uric acid, the final product of purine metabolism (Bogdanov et al 2008;Johansen et al 2009). One study showed that levels of uric acid are negatively associated with PD and disease progression (Bogdanov et al 2008;Johansen et al 2009).…”
Section: Parkinson's Disease (Pd Mim168600) Pd Is the Second Most Cmentioning
confidence: 99%
“…Two metabolic profiling studies of PD patients reveal decreased plasmatic levels of the antioxidant uric acid, the final product of purine metabolism (Bogdanov et al 2008;Johansen et al 2009). One study showed that levels of uric acid are negatively associated with PD and disease progression (Bogdanov et al 2008;Johansen et al 2009). Also levels of glutathione were increased strongly reinforcing the contribution of oxidative stress to HD (Bogdanov et al 2008;Johansen et al 2009).…”
Section: Parkinson's Disease (Pd Mim168600) Pd Is the Second Most Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these findings showed that LRRK2 patients with the G2019S mutation have unique metabolomic profiles that distinguish them from patients with idiopathic PD. More importantly, asymptomatic LRRK2 carriers can be separated from gene negative family members, which raise the possibility that metabolomic profiles could be useful in predicting which LRRK2 carriers will eventually develop PD [57]. By using inductively coupled plasma-atomic emission spectrophotometry (ICP-AES) and inductively coupled plasma mass spectrometry (ICP-MS) to determine the concentration variations of elements between PD and normal samples, an element linkage map was established.…”
Section: Metabolomicsmentioning
confidence: 99%